LEGAL PROBLEMS AND PRACTICE OF ONE-SIDED TERMINATION OF A PROFESSIONAL SPORTS COACHING CONTRACT BY A COACH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
In modern professional sports, the relationship between a coach and a sports club (or federation) possesses a complex legal nature and is governed by both labour law and specific norms of sports law. In practice, the unilateral termination of a contract by a club (for example, due to unsatisfactory sporting results) is a common occurrence and has been widely examined. However, the unilateral termination of a contract by a coach has been comparatively under-researched, despite constituting a pressing legal issue that may lead to highly contentious consequences in practice.